Pre-Service Teachers': Analysis and Constraints in Making HOTS-Based Multiple Choice Questions - Yolida, Berti; Marpaung, Rini Rita T; Lengkana, Dewi (Journal of Education for Sustainability and Diversity, 2023)
Students in pre-service teacher education have difficulty formulating questions, particularly HOTS questions. The purpose of this study was to describe the distribution of questions, the percentage of HOTS (Higher Order Thinking Skills) questions, and the obstacles faced by pre-service teachers in creating HOTS-based questions. The research method uses qualitative methods with descriptive data presentation. The research was conducted at the Biology Education Study Program with a sample of 2020 pre-service teachers, with 57 pre-service teachers selected by purposive sampling. The data source is multiple-choice questions made by pre-service teachers and tested on students in pilot schools in Lampung Province, Indonesia. The results of the study showed that 72.46% of the questions were in the valid category and 18.84% of the HOTS questions were in the low category. The obstacles found were difficulties in compiling questions, especially HOTS questions, difficulties in making homogeneous alternative answers, and distractors.